2016
DOI: 10.1242/jcs.178723
|View full text |Cite
|
Sign up to set email alerts
|

DNA replication initiator Cdc6 also regulates ribosomal DNA transcription initiation

Abstract: RNA-polymerase-I-dependent ribosomal DNA (rDNA) transcription is fundamental to rRNA processing, ribosome assembly and protein synthesis. However, how this process is initiated during the cell cycle is not fully understood. By performing a proteomic analysis of transcription factors that bind RNA polymerase I during rDNA transcription initiation, we identified that the DNA replication initiator Cdc6 interacts with RNA polymerase I and its co-factors, and promotes rDNA transcription in G1 phase in an ATPaseacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 50 publications
3
25
0
3
Order By: Relevance
“…There is a growing possibility that ribosome biogenesis and DNA replication, two very fundamental cellular processes, are linked together. Previously, hIPI3 and hCDC6, as well as Noc3p and Ipi3p in budding yeast, were found to play roles in both DNA replication and ribosome biogenesis [6,38,55]. Similarly, hNOC3 may also be involved in the intracellular transport of the ribosome subunits, like yeast Noc3p.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing possibility that ribosome biogenesis and DNA replication, two very fundamental cellular processes, are linked together. Previously, hIPI3 and hCDC6, as well as Noc3p and Ipi3p in budding yeast, were found to play roles in both DNA replication and ribosome biogenesis [6,38,55]. Similarly, hNOC3 may also be involved in the intracellular transport of the ribosome subunits, like yeast Noc3p.…”
Section: Discussionmentioning
confidence: 99%
“…We also demonstrate that defects in ribosome biogenesis, by specific inhibition of the ribosome biogenesis pathway through knockdown of RPA194 (the largest subunit of RNA polymerase I) or treatment with the RNA polymerase I inhibitor CX-5461, did not result in any observable defect in pre-RC assembly, EdU incorporation or cell cycle progression within a comparable timeframe. Therefore, hNOC3, like hIPI3 and hCDC6 [6,38], plays an essential role in replication licensing and may also serve to coordinate DNA replication and ribosome biogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Cell division cycle 6 homolog ( CDC6 ) is involved in the initiation of DNA replication and participates in checkpoint controls that ensure DNA replication is completed before mitosis is initiated. Huang et al [ 47 ] reported that DNA replication initiator CDC6 also activated ribosomal DNA transcription initiation during cell cyle at G1/S (start) transition. High expression of CDC6 in epithelial ovarian cancer (EOC) cells was indicated as a new potential therapeutic target for EOC patients [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides increased origin firing and DNA rereplication, CDC6-induced replication stress can also occur through collision between replication and transcription machineries and formation of R-loops (Komseli et al, 2018). Interestingly, R-loop formation caused by CDC6 overexpression is preferentially observed within the nucleoli, consistent with the fact that CDC6 is important for transcriptional regulation of the highly repetitive heterochromatic ribosomal DNA (rDNA) (Huang et al, 2016). As a result of replication stress, CDC6 upregulation causes a number of structural and numerical chromosome aberrations in different models, with the majority of breakpoints located at CFS (Liontos et al, 2007;Sideridou et al, 2011;Komseli et al, 2018).…”
Section: Cdc6mentioning
confidence: 78%